Un proiect unic în lume N. Iorga descoperă tipărituri românești cu mult mai vechi decât cele știute - I. Oprișan (Revista de Istorie și Teorie Literară)
The article mainly reveals N. Iorga’s exceptional method of discovering texts printed on the territory of Romania much older than those known, by opening the spines of used church books, in which there were – as filling – sheets from previous printings. Examples are given and the help received by the historian from all over the country is cited.